Stress distribution is susceptible to the angle of the osteotomy in the high oblique sagittal osteotomy (HOSO): biomechanical evaluation using finite element analyses. Issue 1 (20th May 2021) - Carlos, Herrera-Vizcaíno; Marta, Baselga Lahoz; Orlando, Pelliccioni Monrroy; Samuel, Udeabor E; Sader, Robert; Seifert, Lukas Benedikt
Abstract: Aim: This computational study aimed to evaluate the influence of the angle of the osteotomy when performing a high oblique sagittal osteotomy over the distribution of stress to the osteosynthesis plates and mandibular segments. Material and methods: For this purpose, a finite element analysis of different combinations was carried out based on the osteotomy angle and mandibular mobilization using Autodesk Inventor® resulting in a total of 72 simulations. To check the correlation between the osteotomy angles with respect to the tension in the mandibular structure in different mobilizations, a student t-test was used. Results: The results of the advancement mobilizations (2.5 mm to 5.5 mm) reported increasing values for tension in the probe of the fourth screw and in the probe of the plate surface as the osteotomy angle increased (p-value <10-8). The results of the setback mobilizations (−2.5 mm to −5.5 mm) show comparable values (p-value <10-8). The resulting contact surface between bone segments varies depending on the osteotomy angle, increasing 44.67% from 45° to 70° and decreasing 22.05% when the angle is reduced to 30°. Conclusion: The angle of the osteotomy is a very relevant parameter in the design of the studied mandibular osteotomy, since the distribution of the reported stresses is substantially susceptible to its variation.